Membangun Ahklak Mulia Melalui Konseling Islami; Analisis Literatur Tentang Praktik Konseling Kelompok Dan Individu - Imam Rifai; Dina Hajja; Sumarto; Beni Azwar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the role of Islamic-based group and individual counseling in strengthening students’ character and morals at MTs Muhammadiyah Curup. Islamic counseling integrates psychological principles with Islamic spiritual values to shape students' behavior and personality in accordance with Islamic ethics. The findings indicate that while Islamic counseling approaches have been included in the school’s guidance programs, their implementation remains suboptimal. Contributing factors include low frequency of counseling sessions, a lack of participatory methods, and limited competencies among counselors in systematically applying Islamic counseling techniques. Furthermore, parental and community involvement in the counseling process is minimal. The study recommends specialized training for school counselors, increased frequency of counseling services, and stronger collaboration between schools, parents, and communities to support character development through Islamic counseling. By enhancing the spiritual and emotional dimensions of counseling, the formation of students’ moral character can be achieved more effectively and sustainably.